ISOLASI DAN UJI BIOAKTIVITAS SENYAWA KIMIA DARI TALUS LICHEN USNEA DASYPOGA (ACH.) NYL. - Sri Winiati1, ; Wahyudi Priyono Suwarso2, ; Herry Cahyana2, ; M. Hanafi3, (Matematika dan Sains, 2009)
Two known compounds, namely (-)-usnic acid and eumitrin A1, had been isolated from the lichen Usnea dasypoga (Ach.) Nyl. The molecular structure of all isolates were determined by the spectroscopic data (UV, IR, NMR, MS). The (-)-usnic acid and eumitrin A-1 showed toxicity against Artemia salina with LC50 of 39,52 µg/mL and 2,25 µg/mL, respectively. While two isolates also showed cytotoxycity againts murine leukemia P-388 cells with IC50 of 6,5 µg/mL dan 3,2 µg/mL, respectively.50 of 39,52 µg/mL and 2,25 µg/mL, respectively. While two isolates also showed cytotoxycity againts murine leukemia P-388 cells with IC50 of 6,5 µg/mL dan 3,2 µg/mL, respectively.